It's magical! it's malleable! . . . it's memory. - Neimark, Jill (Psychology Today)
In the past few years, scientists have begun piecing together information about human memory that is stunning in its specifics. Memory is both more complex and more primitive than previously thought. Psychiatrist Daniel Siegel notes that the “parallel processing involved in memory is so complex we can't even begin to think how it works.” The article discusses the role of the brain's hippocampus in memory, how and when memories become permanent, what happens when memories go awry and how to treat this problem, losing and regaining memory, and whether memory can create the self.